How do Geohazards Affect Household Consumption: Evidence From China - Zhao, Luman; Zhu, Boyi (Frontiers in Earth Science, 2022)
Geohazards trigger well-documented adverse effects on human health and economic development. However, previous studies mostly focused on the impact of one specific geohazard on consumption and discussed the impact mechanism from a limited perspective. In this paper, we focus on the consequences of generalized geohazards on household consumption in China and investigate the mechanisms of the impact of geohazards on consumption from three perspectives by using the China Household Finance Survey (CHFS) 2017 microdata and National Bureau of Statistics provincial-level data. The study finds that, firstly, household consumption is significantly higher in areas with more geohazards and the effect is found to be long-term. This finding passes a series of robust tests. Secondly, heterogeneity analysis reveals that the consumption structure of families is changed by geohazards. Moreover, the frequency of geohazards affects the consumption of households at different income-level to different degrees. Thirdly, among three possible impact mechanisms, the main mechanism of the impact of geohazards on household consumption is through the increasing of individuals’ impatience.